Cognitive Behavioral Approach to Treat Obesity: A Randomized Clinical Trial - Moraes, Amanda dos Santos; Padovani, Ricardo da Costa; La Scala Teixeira, Cauê Vazquez; Cuesta, Maria Gabriela Soria; Gil, Silvandro dos Santos; de Paula, Bárbara; dos Santos, Gilberto Monteiro; Gonçalves, Rodrigo Tributino; Dâmaso, Ana Raimunda; Oyama, Lila Missae; Gomes, Ricardo José; Caranti, Danielle Arisa (Frontiers in Nutrition, 2021)
Aim: our aim was to analyze and compare the effects of three different long-term treatments on anthropometric profiles, eating behaviors, anxiety and depression levels, and quality of life of groups of adults with obesity. Methods: The forty-three participants in the study were randomly assigned to one of three groups: the education and health group (EH, n=12), which received lectures on health topics; the physical exercise group (PE, n=13), which underwent physical training; and the IT+CBT (n=18) group, which received physical training, nutritional advice and physical and psychological therapy. Results: Total quality of life increased significantly in the EH group (Δ=2.00); in the PE group, body weight significantly decreased (Δ=-1.42) and the physical domain of quality of life improved (Δ=1.05). However, the most significant changes were seen in the IT+CBT group, in which the anthropometric profile improved, there was an increase in quality of life in all domains (physical, psychological, social, and environmental), an improvement in eating behaviors (DEBQ, total Δ=-8.39) and a reduction in depression (BDI, Δ= -10.13). Conclusion: The IT+CBT program was more effective than the PE and EH programs.